2020
DOI: 10.23939/jtbp2020.01.088
|View full text |Cite
|
Sign up to set email alerts
|

Оrto-Phosphoric Acid as an Alternative to Hydrochloric Acid – For Cationic Bitumen Road Emulsions. Review

Abstract: In this article the cationic bitumen emulsions are characterized-as popular binder for various road emulsions. There are considered the specific features of cationic bitumen road emulsions' formulations. There are presented the functions and specificities of the acids application in cationic bitumen road emulsions. The literary review is presented on potentialities of ortho-phosphoric acids application instead of the traditional hydrochloric acid. Chemical peculiarities of application are presented (as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…For further testing, the slurry-surfacing mix No. 3 was rejected, as far as the rates of cohesion strength buildup for the mix 0-5 mm were unsatisfactory in contradistinction to the investigations results [21,22]. Thus, the formulation of bitumen emulsion No.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…For further testing, the slurry-surfacing mix No. 3 was rejected, as far as the rates of cohesion strength buildup for the mix 0-5 mm were unsatisfactory in contradistinction to the investigations results [21,22]. Thus, the formulation of bitumen emulsion No.…”
Section: Resultsmentioning
confidence: 96%
“…It was noted that total surface activity determined by the methylene blue index (MB) is 15 ml, which exceeds the allowable norm (5-10 ml). However, previous studies [21,22] have indicated that slurry-surfacing mixtures on orthophosphoric acid make it possible to use an aggregate with high MB values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of scientific literature data has shown that the modern scientists pay the major attention to the study of bitumen emulsion component (with regard to surface dressing technology) (Zhdaniuk, 2008;Solodkyy, 2018;Sidun, 2020), as well аs to the methods for evaluation of adhesion between the components of surface dressing and non-skid qualities on the surface dressing done Pavlyuk, 2010;Pavlyuk, 2013).…”
Section: Introductionmentioning
confidence: 99%